Unicuspid Aortic Stenosis in a Patient with Turner Syndrome: A Case Report - Essandoh, Michael; Castellon-Larios, Karina; Zuleta-Alarcon, Alix; Portillo, Juan Guillermo; Crestanello, Juan A. (Frontiers in Cardiovascular Medicine, 2014)
Congenital aortic valve anomalies are the cause of premature aortic stenosis in pediatric and younger adult populations. Despite being very rare, unicuspid aortic valves account for approximately 5% of isolated aortic valve replacements. Patients with aortic stenosis, present with the same symptomatology independent of leaflet morphology. However, the presence of bicuspid and unicuspid aortic stenosis is associated with a higher incidence of aortopathy, especially in Turner syndrome patients. Turner syndrome, an X monosomy, is associated with aortic valve anomalies, aortopathy, and hypertension. These risk factors lead to a higher incidence of aortic dissection in this population. Patients with Turner syndrome and aortic stenosis that present for aortic valve replacement should therefore undergo extensive aortic imaging prior to surgery. Transthoracic echocardiography is the diagnostic tool of choice for valvular pathology, yet it can misdiagnose unicuspid aortic valves as bicuspid valves due to certain similarities on imaging. Transesophageal echocardiography is a better tool for distinguishing between the two valvular abnormalities, although diagnostic errors can still occur. We present a case of a 50-year-old female with history of Turner syndrome and bicuspid aortic stenosis presenting for aortic valve replacement and ascending aorta replacement. Intraoperative transesophageal echocardiography revealed a stenotic unicommissural unicuspid aortic valve with an eccentric orifice, which was missed on preoperative imaging. This case highlights the importance of intraoperative transesophageal echocardiography in confirming preoperative findings, diagnosing further cardiac pathology, and ensuring adequate surgical repair.